THE COVID-19 PANDEMIC EXPLOITED BY EXTREMISTS: A COMPARATIVE STUDY BETWEEN INDONESIA AND GERMANY - Praditya, Yosua (Indonesian Association for International Relations, 2023)
This article aims to show that extreme groups, including their sympathizers, delegitimize the government by exploiting radical narratives during the Covid-19 pandemic. Two countries, namely Indonesia and Germany, as examples in a comparative study through qualitative methodology with risk society theory and conspiracy narratives. The results of the study show four findings, namely (1) the resistance response of extreme groups to the government increased during Covid-19; (2) online dissemination of radical narratives is increasing in both Indonesia and Germany; (3) the characteristics of extreme groups and their sympathizers are almost the same in Germany and Indonesia; and (4) the social life of society that coexists with technology is an entry point for extreme groups on social media. In conclusion, in the future, extreme groups and their sympathizers will always optimize their agenda online, because they succeeded in doing so during the implementation of the Covid-19 social restrictions.